1963
DOI: 10.1097/00004032-196302000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Human Tissue Part II. Adult Subjects from the United States

Abstract: Central values and an estimate of the variation about the central values are given for 24 trace elements and the dry, and ash content of samples of 29 different tissues of 150 adult victims of instantaneous death who had spent their lives in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
2

Year Published

1969
1969
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(90 citation statements)
references
References 3 publications
9
72
0
2
Order By: Relevance
“…The reliable data on trace element mass fractions in normal geriatric thyroid is apparently extremely limited. There are many studies regarding trace element content in human thyroid, using chemical techniques and instrumental methods [25][26][27][28][29][30][31][32][33][34][35][36]. However, the majority of these data are based on measurements of processed tissue and in many studies tissue samples are ashed (are burned in a muffle furnace) before analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The reliable data on trace element mass fractions in normal geriatric thyroid is apparently extremely limited. There are many studies regarding trace element content in human thyroid, using chemical techniques and instrumental methods [25][26][27][28][29][30][31][32][33][34][35][36]. However, the majority of these data are based on measurements of processed tissue and in many studies tissue samples are ashed (are burned in a muffle furnace) before analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension in response to cadmium was substantiated by two later studies (Schroeder 1964a;Schroeder and Buckman 1967a). A potential role of cadmium as a human hypertensive agent was indicated by Schroeder's (1964b) analysis of autopsy data collected by Tipton and Cook (1963) which indicated a presence of high cadmium-to-zinc ratios in cadavers of hypertensive subjects. Direct vasoconstriction and increased cardiac output were suggested as mechanisms for the induction of hypertension by cadmium, based again on experiments with rats (Perry et al 1967).…”
Section: Cadmium and Zinc Levels In The Hair Of Smokers And Nonsmokermentioning
confidence: 99%
“…Inorganic hexavalent forms such as molybdenum trioxide, sodium molybdate, and ammonium molybdate are readily absorbed from both food and water, whereas molybdenite i s not. Human absorption rates of 40 t o 70 percent have been observed for the soluble forms of molybdenum (Tipton et ai., 1969;Robinson et al, 1973;Alexander et al, 1974).…”
Section: 210mentioning
confidence: 99%
“…The International Commission on Radiological Protection estimate for the absorption of soluble vanadium compounds is 2 percent (ICRP, 19601, but the World Health Organization states that absorption of even very soluble forms of vanadium is less than 1 percent from the gastrointestinal tract (WHO, 1988). Limited human data (from three individuals) have suggested that as much as 10 percent of a repeated oral dose may be absorbed (Proescher et at., 191 7;Tipton et al, 1969). Soluble vanadium compounds that are inhaled and deposited are more Vanadium is an element and is not metabolized.…”
Section: Vanadium Absorotionmentioning
confidence: 99%